Al-Mata Sports Center / Nabil Iqbal Yuslan ... [et al.] - Yuslan, Nabil Iqbal; Bahrulashikin, Azad Hazim; Azman, Ammar; Mohd Azhari, Muhammad Aiman Hakimi; Sanusi, Mohamad Firdaus (2022)
The sport attire business run by Al-Mata is managed by five top managers and the lead of the management is the General Manager. The administration plan will describe the task and responsibilities for each manager in the company. The administration is also responsible in protecting employee welfare and safety in terms of income, benefits, providing good office furniture and fittings and safety equipment. The administration plan will also include schedule of remuneration and administration budget allocated for running the business.